2018
DOI: 10.1002/biof.1431
|View full text |Cite
|
Sign up to set email alerts
|

Wasabi 6‐(methylsulfinyl)hexyl isothiocyanate induces apoptosis in human colorectal cancer cells through p53‐independent mitochondrial dysfunction pathway

Abstract: 6-(Methylsulfinyl)hexyl isothiocyanate (6-MSITC), a major bioactive compound in Wasabi [Wasabia japonica (Miq.) Matsum.], has revealed the inhibitory effect on colon carcinogenesis in rat cancer model although the underlying mechanism is unclear. In this study, we used two types of human colorectal cancer cells (HCT116 p53 and HCT116 p53 ) to investigate the anticancer activity and molecular mechanisms of 6-MSITC. Interestingly, 6-MSITC inhibited the cell proliferation in both types of cells with similar IC va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…The mode of cell death was through two distinct pathways involving autophagy and mitotic arrest. It has been reported that 6-MITC possesses antitumor characteristics through the inhibition of nuclear factor-kappaB (NF-κB) pathway, the disturbance of mitochondrial function, and finally, the induction of cell apoptosis in different cancer cells [27,28]. Previously, we found that 6-MITC acted against tumor cell growth through mitotic arrest, the induction of apoptosis, and the inhibition of the expression of SOX2, a cancer stem cell molecule in human pancreatic cancer cells [26].…”
Section: Discussionmentioning
confidence: 94%
“…The mode of cell death was through two distinct pathways involving autophagy and mitotic arrest. It has been reported that 6-MITC possesses antitumor characteristics through the inhibition of nuclear factor-kappaB (NF-κB) pathway, the disturbance of mitochondrial function, and finally, the induction of cell apoptosis in different cancer cells [27,28]. Previously, we found that 6-MITC acted against tumor cell growth through mitotic arrest, the induction of apoptosis, and the inhibition of the expression of SOX2, a cancer stem cell molecule in human pancreatic cancer cells [26].…”
Section: Discussionmentioning
confidence: 94%
“…6-MITC has many functions, including neuroprotection [ 18 ], anti-inflammation [ 19 ], anti-pulmonary metastasis [ 1 ], chemoprevention [ 2 , 20 ], and cancer prevention [ 3 , 21 , 22 ]. The mechanisms of 6-MITC inhibit tumor growth through the disruption of mitochondrial function or the inhibition of the NF-κB pathway by abrogating the PI3K/AKT pathway to induce apoptosis [ 22 , 23 ] and sensitizing the anti-tumor agent to augment cell killing [ 17 ]. During the cell cycle, the G2/M phase is more sensitive to radiation than other cell cycle phases and more sensitive in the mitotic phase compared to the G2 phase.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation of the neuroprotective effect on IMR-32 human neuroblastoma cells was conducted by Trio et al, who concluded that 6-(methylsulfinyl)hexyl ITC can exert a neuroprotective effect by activating the Nrf2-mediated oxidative stress response pathway [27]. Likewise, 6-(methylsulfinyl)hexyl ITC showed inhibitory effect on colon carcinogenesis through a p53-independent mitochondrial dysfunction pathway [28]. Inhibition of viability, accompanied by the features of mitotic arrest and apoptosis of human pancreatic cancer cell lines PANC-1 and BxPC-3 were also observed for 6-(methylsulfinyl)hexyl ITC [29].…”
Section: Cytotoxic Activitymentioning
confidence: 99%